Dukungan Teknologi Pengembangan Ubi Kayu di Sumatera Barat - Atman Atman (Politeknik Negeri Lampung., 2011)
Role of cassava in the national economy continued to decline because it is not a priority commodity. As a result, crop acreage is declining and productivity did not increase significantly. This situation also occurred in West Sumatra Province. The cause is not yet precise technology to increase the income of cassava farmers and the diversity of the community's ability to adjust the pattern that has been owned by the available land resources. Meanwhile, demand for cassava will continue to increase along with the continued rise and soaring fuel prices (fuel) in the world market for cassava is one source of bio-ethanol to substitute a premium. This article contains about the problems of cassava and technological support for the development of cassava in West Sumatra. The methodology of writing a book study (literature) on cassava commodity that comes from books, proceedings, journals, papers and others. As a result, the development of cassava in West Sumatra to be directed mainly on dry land agroecosystem. Based on the type of climate and land type, almost all areas in West Sumatra has the potential to be developed as a regional center for cassava production.To improve cassava production strategies are needed, among other things: (1) The addition of harvest area, and (2) Intensification of quality improvement. Addition of harvest area include: (a) opening of a new land, (b) multiple cropping, and (c) increase harvest index. While improving the quality of intensification can be done with the application of several alternative technologies in cultivation, among others: (1) high yielding varieties, (2) preparation of seedlings, (3) land preparation, (4) planting, (5) fertilization, (6) plant maintenance; and (7) harvest. Results of analysis of farming cassava variety Darul Hidayah show farmers the benefits of Rp. 34,110,000, - for 12 months and R/C ratio value = 3.46. Keywords: cassava, technology, dry land, culture, West Sumatra.